Assessing the Impact of Topical Steroids on Tinea Infections: An Epidemiological Investigation - Gauri H. Uplenchwar1 (International Journal of Vaccines, 2024)
This retrospective epidemiological study investigates the prevalence and characteristics of modified tinea infections resulting from the use of topical steroids. Analyzing patient records from October 2022 at ‘District General Hospital, Amravati, the study reveals a significant association between topical steroid use and altered clinical features in 89% of cases. Factors such as steroid potency, duration of use, and specific tinea subtypes affected contribute to understanding the epidemiology of modified tinea infections. Patient counseling plays an important role in the fast recovery of such patients. Healthcare providers should take into account the past use of steroids when diagnosing and treating tinea infections, underscoring the importance of additional research to guide evidence-based protocols. It is recommended that medical professionals consider the patient's past use of steroids while identifying and treating tinea infections. This emphasizes the need for more investigation to clarify the specifics of this relationship and to guide evidence-based practices. These kinds of studies are essential for expanding our knowledge of the difficulties associated with identifying and treating tinea infections, which will ultimately lead to better patient treatment and results. Through the integration of findings from both this study and upcoming research endeavors, medical professionals will be able to formulate more knowledgeable strategies for the diagnosis and treatment of tinea infections, which will maximize treatment effectiveness and foster patient welfare.
Keywords: Corticosteroids; Dermatophytes; Steroid-modified tinea; Tinea incognito; Topical steroid misuse